2008
DOI: 10.1111/j.1753-6405.2008.00166.x
|View full text |Cite
|
Sign up to set email alerts
|

The mental health of Australian mothers and fathers of young children at risk of disability

Abstract: Objectives: To: (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
35
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 35 publications
(98 reference statements)
2
35
1
Order By: Relevance
“…However, recent research has suggested that poorer well-being among parents of children with disabilities may be attenuated or even eliminated when appropriate methods are used to control for between-group differences in family socioeconomic circumstances (Emerson, Hatton, Blacher, Llewellyn, & Graham, 2006;Emerson & Llewellyn, 2008;Olsson & Hwang, 2008).…”
mentioning
confidence: 98%
“…However, recent research has suggested that poorer well-being among parents of children with disabilities may be attenuated or even eliminated when appropriate methods are used to control for between-group differences in family socioeconomic circumstances (Emerson, Hatton, Blacher, Llewellyn, & Graham, 2006;Emerson & Llewellyn, 2008;Olsson & Hwang, 2008).…”
mentioning
confidence: 98%
“…These consequences arise because looking after a child with a disability is very difficult and families are not prepared for it (1). Families with children with disabilities experience very high levels of stress and depression (2–4). Throughout their lives, parents of these children report a wide array of difficult emotions: protectiveness towards someone helpless; revulsion at the abnormal; reproductive inadequacy; child-rearing inadequacy; anger; grief; shock; guilt; and embarrassment (5).…”
mentioning
confidence: 99%
“…These include child factors, such as age, sex, type of disability, caregiving ‘burden’, the presence of externalising behaviour problems, and emotional disorders. Parental factors, such as personality and coping styles, and social factors, such as marital harmony, social support, and socio-economic circumstances, also play an important part (4). …”
mentioning
confidence: 99%
“…Social adjustment means person's adjustment with the social environment that can be created by adapting the self to the environment to satisfy needs [10]. Lack of social relations that occurs due to undesired social adjustment can cause negative effect on incentive and psychological health of the person [11] and leads to weak psychological functioning such as feel guilty, negative self-concept, low self-esteem, isolation, and low life satisfaction [12].…”
Section: Introductionmentioning
confidence: 99%